Design Of Covid-19 Learning Media Based On 2D Video Using 3D Unity: Design Of Covid-19 Learning Media Based On 2D Video Using 3D Unity - Dimas Tri Pamungkas; Ucuk Darussalam; Endah Tri Esti Handayani (Jurnal Mantik, 2020)
Making of this application utilizes Unity 3D software and Visual Studio 2010 using the SDLC (Software Development Life Cycle) method which is applied in the prevention and management application of Covid-19, therefore making this application aims to provide education to the public regarding how to prevent and cope with Covid-19 which is also an example of animation to facilitate the public in understanding the education. And the results obtained by the community are quite helpful with the application in which there is an animated video